2020
DOI: 10.1002/ese3.607
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and mechanism research of a new low molecular weight shale inhibitor on swelling of sodium montmorillonite

Abstract: Shale gas as green and clean energy is attracting more interest. However, shale hydration and swelling have become the major challenges using water‐based drilling fluids, replacing oil‐based drilling fluids, for developing shale gas. In this work, a low molecular weight branched polyamine (NETS) as clay swelling inhibitor was synthesized. The NETS performed excellent inhibition property by linear expansion experiments and cuttings hot‐rolling recovery. The inhibition mechanism of NETS was investigated using X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Note that in the high-throughput screenings below, natural gas is approximated as methane. As a caveat, a computational study by Zhang et al found that, when considering the influence of larger hydrocarbons contained in natural gas, the ranking of MOFs for natural gas storage could differ from when approximating natural gas as pure methane [212].…”
Section: Survey Of High-throughput Computational Screenings With Expementioning
confidence: 99%
“…Note that in the high-throughput screenings below, natural gas is approximated as methane. As a caveat, a computational study by Zhang et al found that, when considering the influence of larger hydrocarbons contained in natural gas, the ranking of MOFs for natural gas storage could differ from when approximating natural gas as pure methane [212].…”
Section: Survey Of High-throughput Computational Screenings With Expementioning
confidence: 99%
“…However, the high cost and high environmental load of OBDF greatly limit its application. 11,12 The new generation of SBDF has greatly improved compared with OBDF in terms of performance and environmental protection. For example, ester-based drilling fluid (EBDF) with biodiesel (monoalkyl ester) as the base oil has a higher flash point than OBDF, and most importantly, it has a huge advantage in environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the action of shale and water in the drilling fluid can easily cause the well wall to collapse and trap drills. , Oil-based drilling fluids (OBDF) and synthetic-based drilling fluids (SBDF) are the best choice for reducing shale hydration and swelling problems, because the oil phase in them is generally considered to have an extremely low coefficient of friction. However, the high cost and high environmental load of OBDF greatly limit its application. , The new generation of SBDF has greatly improved compared with OBDF in terms of performance and environmental protection. For example, ester-based drilling fluid (EBDF) with biodiesel (monoalkyl ester) as the base oil has a higher flash point than OBDF, and most importantly, it has a huge advantage in environmental protection. However, the upper temperature limit of the biodiesel invert emulsion for applications is 135 °C, which indicates that its application at high and ultrahigh temperatures needs further research .…”
Section: Introductionmentioning
confidence: 99%
“…30 Recently, the use of ultra-low-molecularweight organic clay stabilizers in WBFs has been suggested as the best choice for all types of shale formation. 31,32 Again, the move toward compounds that leave little or no environmental footprints is increasing due to the stringent rules from environmental agencies. 33,34 The search for monomeric organic compounds from natural extracts, with shale inhibition potentials similar to or better than the conventional clay stabilizers, like KCl, is on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in cases where the smectite composition in the shale formation is higher, KCl exhibits limited performance . Recently, the use of ultra-low-molecular-weight organic clay stabilizers in WBFs has been suggested as the best choice for all types of shale formation. , …”
Section: Introductionmentioning
confidence: 99%